Reatividade de anticorpos IGE específicos a componentes antigênicos de strongyloides ratti por elisa e immunoblotting na estrongiloidíase humana - Rodrigues, Rosângela Maria (2002)
Strongyloidiasis is a worldwide parasitic disease of importance in tropical and subtropical countries. Although primarily restricted to the gastrointestinal tract, hyperinfection and disseminated disease can occur and cause death. This study aimed to evaluate the profile of Strongyloides antigenic components recognized by specific IgE antibodies in serum samples of patients with strongyloidiasis, by using Strongyloides ratti saline extract as heterologous antigen in Immunoblotting (IB) and to compare it with ELISA. S. ratti filariform larvae were obtained from culture of feces of experimentally infected Rattus rattus and harvested by the Baermann-Moraes method. A total of 126 serum samples were analyzed, 50 serum samples of patients who were shedding S. stercoralis larvae in feces (group I), 38 sera of patients with other intestinal parasitoses (group II), and 38 sera of subjects with negative results in three parasitologic assays (group III, copronegative). Leveis of specific IgE to Strongyloides were measured by indirect ELISA in all serum samples and the antigenic components were detected by IB in 50 serum samples of group I, 10 of group II, and 10 of group III. Leveis of IgE expressed in ELISA index (EI) were significantly higher in patients of group I (132.2) than in group II (51.4) and group III (80.7), with positivity rates of 54%, 0% and 10.5%, respectively. Fifteen antigenic components were recognized antigenic (101, 81,70,63,61, 57,54,44,39,36,33,28,19,15 e 7 kDa)by IgE Mtíi-Strongyloides by IB in the group I, with frequency ranging from 8% to 46%. In contrast, in the group II, only 2 antigenic bands (101 and 81 kDa) were detected in a frequency of 10% and no reactivity was found in the group III. The frequency of the antigenic band of 101 kDa in the group I (46%) was significantly higher than in groups II (10%) and III (0%). No difference was found when comparing the frequency of the 81 kDa band in the group I (36%) and group II (10%). When analyzing the ELISA-IgE results in relation to reactivity of antigenic components by IB-IgE to Strongyloides in the group I, sera with EI > 500 recognized 15 immunodominant components whereas sera with EI from 149 to 499 recognized 7 immunodominant bands (101, 81, 70, 63, 61, 44 and 7 kDa). Thus, it can be suggested that these immunodominant antigenic components recognized by IgE wú-Strongyloides might be considered as important markers for serodiagnosis of human strongyloidiasis.